IDENTIFIKASI FAKTOR YANG MELATARBELAKANGI KOMPETENSI PROFESIONALISME GURU SMP NEGERI 4 BANGSALSARI JEMBER (IKIP PGRI Jember, 2018)
This study aims to analyze the factors that influence the professional competence of the teachers at the State Junior High School 4 Bangsalsari Jember with motivation as a moderating variable. The results of the study prove that the educational background, training and development, academic supervision, compensation, utilization of information and communication technology simultaneously have a positive and significant effect on the professional competence of teachers in Bangsalsari 4 Middle School. Overall the education and training background and development have a very big influence on the competence of teachers in SMP Negeri 4 Bangsalsari Jember, while academic supervision, compensation, and utilization of information and communication technology have no significant effect on the professional competence of teachers in Bangsalsari 4 Middle School. Motivation is not able to moderate the relationship between educational background, training and development, academic supervision, compensation, utilization of information technology and communication with the professional competencies of teachers in Bangsalsari 4 Middle School.